Analisis Nilai-nilai Pendidikan Karakter dalam Novel “Love For Show” Karya Andi Eriawan - Dernius Hura (Universitas Nias, 2023)
Novel is one of the literary works written by the author based on himself or other people's experiences. Novels are liked by many people because there are moral values ​​that are useful for everyday life. These moral values ​​relate to character education which has always been considered important for social life. Character education is often considered trivial because the delivery is not as clear as the delivery of formal education. In the novel